Exploring The Attitudes Towards Patients Diagnosed With Alcohol Use Disorder (AUD) -A Qualitative Study Of Nurses At The National Referral Hospital, Bhutan - Chozom, Sangay; Neuhann, Florian; Krahl, Wolfgang (Journal Of Nursing Practice, 2021)
Background: The kind of attitude expressed by the nurses may have significant effect on the recovery process of the patient and on their decision to avail treatment. It is anticipated that by exploring the attitudes of the nurses towards AUD patients and understanding the factors which influences these attitudes, more effective interventions can be developed to provide help and support to this group of patient and also to the nurses in being effective and appropriate in responding to the needs of this group of patient.Purpose: The study was conducted to explore the prevailing attitudes of nurses towards AUD patients, and to further explore the factors influencing these attitudes.Methods: A total of fifteen nurses from Jigme Dorji Wangchuck National Referral Hosiptal were recruited based on convenience and purposive sampling techniques. Qualitative approach was employed by means of conducting face to face in-depth interviews using open ended questions. The qualitative data was analyzed using thematic analysis method.Results: The findings from the study suggest that possessing adequate knowledge on alcohol and addiction, being regularly engaged with AUD patients or having few years of experience working with AUD patients were some of the factors which resulted in more positive attitudes among the nurses. On the contrary, insufficient skills and knowledge related to alcohol addiction and exhibition of aggressive behaviour by the patients could cause negative feelings and ultimately lead to negative attitudes.Conclusion: Therefore, it is of paramount importance that a curriculum on alcohol addiction is introduced in diploma and degree nursing courses offered in Bhutan.